The future of health promotion in schools goes through the strengthening of teacher training at a global level - Jourdan, Didier (2008)
Schools are considered to be settings for both health education and health promotion. But the core business of schools is actually focussed on educational outcomes, not reducing health problems. In most countries, schools give low priority to health promotion and school staffs, mainly teachers, are not aware of their role in health promotion. Studies show that teachers who have received health promotion training tend to be involved more frequently in health promotion projects and have a more comprehensive approach to health education. Pre-service and In-service staff training is then a main challenge. That’s the reason why we have launched an initiative to join international forces to strengthen and advocate for teacher training in health promotion. The main goals are: develop research, affirm and reinforce the work done in teacher training in health promotion, support the institutes/colleges/universities in the provision of initial and in-service teacher training and stimulate international partnership work.